Phaeoacremonium fusiformostromum sp. nov. and a new record of P. croatiense from China - Shang, Qiu-Ju; Hyde, Kevin D.; Liu, Jian-Kui (Phytotaxa, 2021)
Phaeoacremonium species are important pathogens with a worldwide distribution and diverse host and are commonly associated with brown wood streaking, dieback and Esca disease of plants and phaeohyphomycosis of humans. In this study, three sexual taxa, representing two Phaeoacremonium species, were collected from dead wood from Guangdong and Guizhou Provinces in China. Based on the morphological characters and phylogenetic analyses of a combined ACT and TUB2 sequence data, they are identified as Phaeoacremonium fusiformostromum sp. nov., and P. croatiense, which is a new record from China with its first sexual morph. Detailed descriptions and illustrations of these two species are provided, and an updated phylogenetic tree for all Phaeoacremonium species is also given.